An In Vitro Investigation of a Comparison of Bond Strengths of Composite to Etched and Air-Abraded Human Enamel Surfaces - G.B. Gray, BDS, PhD;1 G.P.D. Carey, BDS;2 and D.C. Jagger, BDS, MSc PhD, (Journal of Prosthodontics, 2006)
The purposes of the study were to measure the tensile bond strength of composite resin to human enamel specimens that had been either etched or air-abraded, and to compare the quality of the marginal seal, through the assessment of microleakage, of composite resin to human enamel specimens that had been either etched or air-abraded.